Booth : a novel - Fowler, Karen Joy (G. P. Putnam's Sons, 2022)
"From the Man Booker finalist and bestselling author of We Are All Completely Beside Ourselves comes an epic novel about the family behind one of the most infamous figures in American history: John Wilkes Booth"--